2014
DOI: 10.1007/s00384-014-1901-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for delayed bleeding after endoscopic submucosal dissection for colorectal neoplasms

Abstract: This study demonstrated that location of lesions in the rectum was a significant independent risk factor for delayed bleeding after ESD for colorectal neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 34 publications
3
57
2
1
Order By: Relevance
“…Resection was curative in 16% (6/37) of these T1b CRC patients. In addition, the rate of post-ESD bleeding was 8%, which falls within the range of 0.5-9.5% reported previously for delayed bleeding after colorectal ESD [10]. Moreover, perforation occurred in 2 of our 37 patients (5%), which was in accordance with the findings of other Japanese studies [9,11].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Resection was curative in 16% (6/37) of these T1b CRC patients. In addition, the rate of post-ESD bleeding was 8%, which falls within the range of 0.5-9.5% reported previously for delayed bleeding after colorectal ESD [10]. Moreover, perforation occurred in 2 of our 37 patients (5%), which was in accordance with the findings of other Japanese studies [9,11].…”
Section: Discussionsupporting
confidence: 81%
“…ESD is a reliable method for en bloc resection regardless of the lesion size or location [6,7,8,9,10,11], and is considered useful for T1 CRC as a total excisional biopsy [8]. Here we retrospectively evaluated the outcomes of cT1b CRCs resected by ESD as total excisional biopsy and the utility of ESD to afford complete resection of the lesions, which is essential for establishing a precise histopathological diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although blood vessel density differs in the colon and rectum, its association with vascular invasion remains unclear. It has been reported that tumor location in the rectum is a significant independent risk factor for delayed bleeding following endoscopic submucosal dissection for colorectal neoplasms, potentially as a consequence of differences in blood vessel density (24). Guidelines from the National Comprehensive Cancer Network, the European Society for Medical Oncology and JSCCR identify vascular invasion as a risk factor for lymph node metastasis and recommend that such patients undergo surgery with lymph node dissection (2,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic submucosal dissection (ESD) has been a reliable method for en-bloc resection of colorectal tumors regardless of lesion size [Tanaka et al 2007[Tanaka et al , 2008[Tanaka et al , 2012[Tanaka et al , 2013Tamegai et al 2007;Saito et al 2010;Oka et al 2010Oka et al , 2015aOka et al , 2015bTerasaki et al 2014;Ninomiya et al 2015]. Although colorectal ESD has been established as a procedure with reproducible safety and efficacy, complications such as bleeding and perforation remain problematic.…”
Section: Introductionmentioning
confidence: 99%